Hänsyn till mark och vatten vid slutavverkning : en fältstudie på känsliga marker - Alton, Tarja (SLU/School for Forest Management, 2015)
The purpose of this study is to investigate if there is enough consideration taken to sensitive forest areas close to water or wetlands during clear cutting assignments, and to estimate the extent of damage made by forestry machines used at that time. A field and literature study is used to show how to improve and prevent the damage made in the wake of the machines. This study is made for Sydved, and shall culminate in a policy to prevent ground damage during their clear cutting assignments. The areas which were part of the field studies were clearcuttings on fine grained soil close to water and wetlands. The purpose was to find out if the water had been affected, what had been done to prevent ground damages and what more could have been done. The results of the field studies show that more work needs to be done to reach up to expectations. More information about the assignment area, better planning of sensitive regions, and strengthening of the main haul roads with brush are some of the improvements that can be done. There is also a need for more exact guidelines, follow-ups and education for everyone involved to have the same goals and understanding to prevent ground damage.